2008
DOI: 10.1111/j.1755-5949.2008.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Characterization of A-582941: A Novel α7 Neuronal Nicotinic Receptor Agonist with Broad Spectrum Cognition-Enhancing Properties

Abstract: Among the diverse sets of nicotinic acetylcholine receptors (nAChRs), the alpha7 subtype is highly expressed in the hippocampus and cortex and is thought to play important roles in a variety of cognitive processes. In this review, we describe the properties of a novel biaryl diamine alpha7 nAChR agonist, A-582941. A-582941 was found to exhibit high-affinity binding and partial agonism at alpha7 nAChRs, with acceptable pharmacokinetic properties and excellent distribution to the central nervous system (CNS). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 77 publications
3
58
0
Order By: Relevance
“…Investigation of potential carcinogenic effects produced no significant findings to suggest any α7-related toxicity. The details of the preclinical validation studies of A-582941 were recently reported [138]. Very recently, Biter et al [139] reported that A-582941 can lead to increased phosphorylation of the inhibitory regulating amino acid residue Ser-9 on the glycogen synthase kinase3β (GSK3β), a major kinase responsible for tau hyperphosphorylation in the neuropathology of tauopathies such as front-temporal dementia and AD.…”
Section: Wyeth/siena Biotechmentioning
confidence: 99%
“…Investigation of potential carcinogenic effects produced no significant findings to suggest any α7-related toxicity. The details of the preclinical validation studies of A-582941 were recently reported [138]. Very recently, Biter et al [139] reported that A-582941 can lead to increased phosphorylation of the inhibitory regulating amino acid residue Ser-9 on the glycogen synthase kinase3β (GSK3β), a major kinase responsible for tau hyperphosphorylation in the neuropathology of tauopathies such as front-temporal dementia and AD.…”
Section: Wyeth/siena Biotechmentioning
confidence: 99%
“…Later, newer agonists of NAChR such as A-582941 were synthesized, which had a much better profile in terms of side effects [17]. The effects of A-582941 were investigated on certain animal models including psychosis, and the promising effect of it was demonstrated in certain studies [18]. It has been shown that A-582941 has beneficial effects on attention, spatial and visual learning and memory in rodents and monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…Selective ␣7 receptor agonists also have been shown to normalize sensory gating deficits in animal models (Stevens et al, 1998;Simosky et al, 2001;Hajós et al, 2005), and a recent human study has provided proof-of-concept for the normalization of auditory gating deficits in schizophrenics (Olincy et al, 2006). Most recently, SSR180711 and A-582941 (Tietje et al, 2008) have been reported as selective ␣7 nAChR agonists with in vivo efficacy in a number of preclinical models predictive of cognitiveenhancing and antipsychotic-like activity including memory retention, memory deficits induced by manipulation of the glutamatergic system, and modulation of dopaminergic and glutamatergic transmission in the prefrontal cortex.…”
mentioning
confidence: 99%